Suppression of FOXM1 sensitizes human cancer cells to cell death induced by DNA-damage. - Marianna Halasi; Andrei L Gartel (PLoS ONE, 2012)
Irradiation and DNA-damaging chemotherapeutic agents are commonly used in anticancer treatments. Following DNA damage FOXM1 protein levels are often elevated. In this study, we sought to investigate the potential role of FOXM1 in programmed cell death induced by DNA-damage. Human cancer cells after FOXM1 suppression were subjected to doxorubicin or γ-irradiation treatment. Our findings indicate that FOXM1 downregulation by stable or transient knockdown using RNAi or by treatment with proteasome inhibitors that target FOXM1 strongly sensitized human cancer cells of different origin to DNA-damage-induced apoptosis. We showed that FOXM1 suppresses the activation of pro-apoptotic JNK and positively regulates anti-apoptotic Bcl-2, suggesting that JNK activation and Bcl-2 down-regulation could mediate sensitivity to DNA-damaging agent-induced apoptosis after targeting FOXM1. Since FOXM1 is widely expressed in human cancers, our data further support the fact that it is a valid target for combinatorial anticancer therapy.